Strategy for Using Information and Communication Technology in PAUD to Build Digital Literacy - Mariana, Annisa Dwi (Jurusan Pendidikan Islam Anak Usia Dini UIN Sunan Gunung Djati Bandung, 2024)
The development of information and communication technology (ICT) has brought about major changes in various aspects of life, including early childhood education (PAUD). Although ICT has the potential to support children's cognitive, social-emotional, and motor development, many PAUD institutions still face obstacles in utilizing it. The problems that arise include limited facilities, a lack of teacher competence in integrating ICT, and a lack of guidance on the healthy and safe use of technology for children. This situation has created a gap between the need for digital literacy in the modern era and the ability of ECE institutions to meet it. This study aims to identify effective strategies for utilizing ICT in supporting the digital literacy of early childhood, analyze the challenges of implementation in PAUD institutions, and provide practical recommendations for teachers, parents, and stakeholders. The research method used is a systematic literature review, which examines relevant literature in the form of journals, books, and articles related to ICT and digital literacy in early childhood. The results of the study show that integrating ICT into early childhood education can improve children's cognitive, social-emotional, and motor skills. The use of interactive educational applications can support the development of digital literacy, although challenges such as limited facilities and a lack of teacher training still exist. This study concludes that effective ICT use strategies can help prepare children for future digital challenges. Collaboration between the government, educational institutions, and parents is essential to optimize the use of ICT in early childhood education.